TO MEET RISING COAL DEMAND INDUSTRY HAS TO INITIATE REQUIRED R& D AND EXPLORE LOOK-AHEAD TECHNOLOGY FOR INTRODUCTION IN MINE - GUPTA, ANUP KRISHNA; DUTTA, AJOY KUMAR; BASU, RITA (IJRDO - Journal of Business Management, 2019)
Coal is conventional and key source of energy. Nearly fifty-five percent of the India’s total energy requirements are met from coal which play an important role in the development of India To meet the growing requirement, production of coal is increasing day by day. It is being used as major resource in Power plants, steel and cement industry. Coal Mining in India has been going on effectively for over last 200 years. Working environment of coal mines are generally hazardous due to causes like flooding, subsidence, roofcollapse, leakage of noxious gases, explosion etc. For this reason mine related accidentsoften take place. Many miners had lost their lives due to accidents. In order to meet up country’s rising coal demand there has been major shift in the method of coal production Specially after nationalization of coal Mines ,coal production has been mainly done from opencast with deployment of heavy machineries. Thishowever has led to increase in productiontogether with enhancement of production cost, wages of employees and price of coal to large extent Simultaneously there has been sharp decrease in the manpower strength .closure of number of underground mines.There has been a positive aspect of decline in the rate of accidents yet the rate of occupational diseases remain almost same.The technologies that have been introduced in phases in coal mines are sophisticated and modern., which include control of operation by computer , GPS, improved underground communication system and robot.Though much costly but in a restricted cases robotic technologies are in the process of introduction specially for safety purpose. In fact coal mining industry has been gradually adopting mechanization leading to automation.